Going from Bad to Worse: Adaptation to Poor Health, Health Spending, Longevity, and the Value of Life - Johannes Schünemann; Holger Strulik; Timo Trimborn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Unhealthy persons adapt to their bad state of health and persons in bad health are usually happier than estimated by healthy persons. In this paper we investigate how adaptation to a deteriorating state of health affects health spending, life expectancy, and the value of life. We set up a life cycle model in which individuals are subject to physiological aging, calibrate it with data from gerontology, and compare behavior and outcomes of adapting and non-adapting individuals. While adaptation generally increases the life-time utility (by about 2 percent), its impact on health behavior and longevity depends crucially on whether individuals are aware of their adaptive behavior, i.e. whether they adapt in a naive or sophisticated way. We also compute the QALY change implied by health shocks and discuss whether and how adaptation influences results and the desireability of positive health innovations.
Keywords: I12; D91; J17; 330